Ultrastructural characteristics of spermatogenesis in Pallas's mastiff bat, Molossus molossus (Chiroptera: Molossidae) - Beguelini, Mateus R. [UNESP]; Taboga, Sebastiao R. [UNESP]; Morielle-Versute, Eliana [UNESP] (Wiley-Blackwell, 2012)
Despite the large number of species, their wide distribution, and unique reproductive characteristics, Neotropical bats have been poorly studied, and important aspects of the reproduction of these animals have not been elucidated. We made an ultrastructural analysis of spermatogenesis in Molossus molossus (Molossidae). The process of spermatogonial differentiation is similar to that found in other bats and is also relatively similar to that of Primates, with three main spermatogonia types: Ad, Ap, and B. Meiotic divisions proceed similarly to those of most mammals, and spermiogenesis is clearly divided into 12 steps, in the middle of the range known for bats (916 steps). Formation of the acrosome is similar to that known from other mammals; however, the ultrastructure of spermatozoa was found to have unique characteristics, including many wavy acrosomal projections on its surface, which seems to be specific for the family Molossidae. Comparing the ultrastructure of the spermatozoon of M. molossus with other bats already study, we observed that three characters vary: morphology of the outer dense fibers, of the perforatorium, and of the spermatozoon head. The great similarity of morphological characters between M. molossus and Platyrrhinus lineatus suggests that M. molossus is more closely related to the Phyllostomidae than to the Rhinolophidae and the Vespertilionidae. Microsc. Res. Tech. 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: Chiroptera; Molossus molossus; Spermatogenesis; Spermiogenesis